Regulation of the shoot apical meristem by metabolic signals and the SnRK1 protein kinase - Lopes, Filipa (2022)
"Plants form new organs throughout their lifetime. This depends on the activity of pluripotent stem cells that reside in microenvironments called meristems. The shoot apical meristem (SAM) is responsible for the development of all above-ground tissues, keeping a fine balance between cell proliferation and differentiation, to enable the continuous production of organs such as leaves, flowers, and the stem.(...)"